2020
DOI: 10.32598/ijpcp.26.1.218.18
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Affective-reconstructive Couple Therapy in Increasing the Trust and Marital Satisfaction of Couples With Remarriage

Abstract: Objectives This study aimed to determine the effectiveness of affective-reconstructive couple therapy in increasing the trust in close relationships and marital satisfaction of couples with remarriage and divorce experience. Methods This is a single-case experimental study with a non-concurrent multiple baseline design. Three distressed couples were selected from among couples with remarriage and divorce experience referred to private and government counseling centers in Ahvaz, Iran, based on inclusion/exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Our findings therefore implies that participants opined that they did not understand their spouse or their spouse did not understand them which is the purpose of communication (Olson et al, 2008). Summarily, findings showed that only half of the participants were maritally satisfied (Azimian et al, 2017;Odinka et al, 2018;Omran et al, 2015;Rajabi, 2010;Zandipour & Momeni, 2011). Previous study among secondary school teachers in Nigeria showed higher level of marital satisfaction compared to participants in our study (Ofovwe et al, 2013).…”
Section: Discussionmentioning
confidence: 64%
“…Our findings therefore implies that participants opined that they did not understand their spouse or their spouse did not understand them which is the purpose of communication (Olson et al, 2008). Summarily, findings showed that only half of the participants were maritally satisfied (Azimian et al, 2017;Odinka et al, 2018;Omran et al, 2015;Rajabi, 2010;Zandipour & Momeni, 2011). Previous study among secondary school teachers in Nigeria showed higher level of marital satisfaction compared to participants in our study (Ofovwe et al, 2013).…”
Section: Discussionmentioning
confidence: 64%
“…In fact, communication patterns play a major role in marital trust and intimacy between couples. Couples who spend more leisure time together, have common hobbies, and engage in more verbal or emotional communication, experience greater marital trust (Avanti & Setiawan, 2022;Rajabi et al, 2021). If emotional schemas can interpret and process emotions show reactions and receive feedback, expression styles and emotional disclosure will significantly affect this process due to interpretations, methods, thoughts, and various models of suppression or engagement, which will directly influence the infidelity process among couples (Leahy, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Communication and communication patterns have been considered in different family therapy theories, one of the T E-ISSN: 3041-8518 approaches that has increasingly gained acceptance in relation to family and family therapy is the Satir communication approach (Carr, 2019). Research evidence shows that the Satir communication approach has a positive and significant effect on emotional non-expression and emotional maturity in divorce-seeking couples (Ghorbani & Bagheri Houseinabadi, 2021), communication skills, emotional expressiveness, and empathy (Boostani-Kashani et al, 2021), resilience, and problem-solving in couples (Ghanbari Hashemabadi et al, 2020); also, Rajabi et al (2020) indicate the effectiveness of couple therapy of the Satir communication approach in increasing marital satisfaction and reducing emotional divorce among couples (Rajabi et al, 2021). Furthermore, Carr (2019), in a study, showed that couple therapy, family therapy, and systematic interventions have a positive and significant effect on solving family problems and conflicts (Carr, 2019).…”
Section: Introductionmentioning
confidence: 99%